A synthesis of a comparative analysis of the effectiveness of strategic environmental assessment between Ireland and Scotland applied to Brazil - Lemos, Rose Mary Teixeira de; Maia, Vitória dos Santos Fontanezi; Roque, Rhayane Carvalho; Mauad, Frederico Fábio; Miranda, Renato Billia de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2023)
Strategic Environmental Assessment (SEA) aims to facilitate both integration and assessment of opportunities and threats for action strategies within the framework of sustainable development. Its stages comprise Screening, which analyzes its need, Scoping, which establishes the range of environmental issues to be covered, Analysis, in which the Environmental Report is prepared, Decision-Making, Follow-up, in which both Monitoring and Follow-up of the assessment are conducted, and finally Consultation. Three types of effectiveness approaches, namely procedural effectiveness, substantive effectiveness, and transactional effectiveness can be identified. This article addresses the effectiveness of SEA in Brazil, Ireland, and Scotland through a comparative analysis, since it enables rich discussions on the subject.